EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION, THINK-PAIR-SHARE, DAN PROBLEM BASED LEARNING DENGAN PENDEKATAN SAINTIFIK PADA MATERI EKSPONEN DAN LOGARITMA DITINJAU DARI KREATIVITAS SISWA KELAS X SMA NEGERI KABUPATEN PACITAN - Suprapto Suprapto; Tri Atmojo Kusmayadi; Imam Sujadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aim of this research was to know the influence of teaching and learning models with the scientific approach toward the students’ achievement in learning mathematics considered from the creativity of the students. Teaching and learning models to be compared were GI, TPS, and PBL. This research was chategorized as a quasi experimental research. The population was all students of grade X MIA public SMAs in Pacitan regency in the year 2014/2015. The sampling technique used was stratified cluster random sampling. The method of data collection were documentation, questionaire, and test. Hypothesis testing was performed using two-way analysis of variance with unequal cells. The conclusions of this research were as follows. 1. The students’ achievement in mathematics given GI-S model was better than those who were given TPS-S model, while the students’ achievement given GI-S was the same as those who were given PBL-S model, and the students’ achievement given TPS-S model was the same as those who were given PBL-S model; 2. The mathematics achievement of the students who had high level creativity was the same as those who had medium level creativity, while those who had high level creativity was better than those who had low level creativity, and the students with medium level gave the same achievement as those with low level creativity; 3. In high level creativity, the students’ achievement in learning mathematics using GI-S model was the same as those using TPS-S and PBL-S models. In medium level creativity, the students using GI-S model gave the same achievement as those using TPS-S and PBL-S models, but the students’ achievement using PBL-S model was better than using TPS-S model. In low level creativity, the students who learned mathematics using GI-S model gave the same achievement as those who used TPS-S and PBL-S models, and the students’ achievement using TPS-S model was the same as those using PBL-S model; 4. In learning mathematics using GI-S model, the students with high, medium, and low level creativity gave the same achivement. In using TPS-S model, the students with high, medium, and low level creativity gave the same achievement. In using PBL-S, the students with high level creativity had the same achievement as those who had medium and low level creativity, but the students with medium level creativity gave better achievement than those who had low level creativity.Keywords: Group Investigation (GI), Think Pair Share (TPS), Problem Based Learning (PBL), Scientific approach, Creativity